Mixed convection and thermal radiation effects on non-Newtonian nanofluid flow with peristalsis and Ohmic heating - Alrashdi, Abdulwahed Muaybid A. (Frontiers in Materials, 2023)
This study investigates the heat and mass transfer characteristics of a non-Newtonian nanofluid comprising graphene nano-powder and ethylene glycol during peristalsis. The Carreau-Yasuda model is used to determine the rheological characteristics of the nanofluid, and the effects of viscous dissipation, Lorentz force, Ohmic heating, and Hall effects are also considered. The analysis includes mixed convection, thermal radiation, and porous medium effects, and the problem is mathematically described using the long wavelength and low Reynolds number approximations. The resulting nonlinear system is solved using numerical methods. The results show that an increase in the Brinkman number, heat source, and thermal slip parameter increases the temperature of the nanofluid, while the heat transfer rate decreases with a higher Hall parameter. The velocity near the center of the channel increases for higher values of the concentration Grashof and Hall parameters, and an increase in the Hall and Brownian motion parameters leads to an increase in the concentration of nanoparticles. These findings can have practical implications in materials science, chemical engineering, and biomedical engineering.